Overboard - Searls, Hank. (New York W. W. Norton and Company, Inc., 1977)
The story of a strong man panicked, a woman fighting to live, and a love gone wrong. Mitch Gordon, lawyer and yachtsman, awakens 70 miles from Tahiti to find himself alone on his 40-foot ketch. Sometime in the last dark hours his wife Lindy has been swept overboard into the giant Pacific swells. For thirty-six hours he clings aloft in the tropical sun, tracing and retracing the vessels course. Lindy, buoyed by a flimsy life-jacket, struggles to survive until he can find her. Their life emerges through flashbacks as he plows back and forth along their track, at times coming very close. Their love, weakened by neglect and things unsaid, has almost foundered, then been salvaged in the shared danger of a hurricane, and now seems bound for tragedy...
Keywords: Fiction